Ethical Horizons in AI: Navigating Opportunities and Upholding Values in the MENA Landscape - Ray Gutierrez Jr. (مجلة النور للدراسات الانسانية)
Artificial intelligence presents immense opportunities to transform the Middle East and North Africa (MENA) region through advances in healthcare, environmental sustainability, economic inclusion, and more. However, the adoption of AI also poses risks if deployed unethically, as seen in biased facial recognition harming vulnerable populations. This paper analyzes AI’s potential while assessing core ethical challenges in the MENA context. It spotlights perspectives from regional experts on grounding AI governance in cultural values, exemplified by initiatives like the UAE’s AI ethics council. Proposed solutions include diversifying AI design teams, auditing for bias, and centering human needs in policymaking. Rather than resist progress, this talk empowers MENA nations to proactively shape an AI landscape that promotes human dignity, community, justice and participatory decision-making. Audiences will gain an understanding of strategies to realize AI’s benefits through an ethical lens. The aim is to provide practitioners and policymakers with an actionable framework to develop and regulate AI systems that align with regional values and elevate society